(untitled) (International Journal of Medical and Surgical Sciences, 2014)
By studying the human genome and advances in molecular biology, currently can predict interactions between the genome and food components in order to obtain information about the role of diet in maintaining health and in the prevention, initiation, development and progression or severity of a disease like obesity. The aim of this review was to present the current understanding of the factors that normally regulate eating behavior alteration, and the mechanisms involved and associated with molecular biology. About 42 genes related to the regulation of feeding, expressing at the nucleus accumbens, ventral tegmental area, nucleus of the solitary tract, the lateral hypothalamus, arcuate nucleus, paraventricular, ventromedial and dorsomedial hypothalamus. There are specific brain mechanisms that regulate hunger and satiety, which would be in constant interaction with mechanisms known as "wanting" and "liking" circuits modulated by reward, pleasure and addiction. The phenotypic expression of eating behavior is complex by genetic variability, whose behavior is defined by the interaction of genetic condition (innate), environmental experience and learning (acquired characteristics), which structured eating behavior. Altering the genes and circuits involved would be involved as a cause in eating disorders.